STUDENTS’ PERCEPTION TOWARD ENGLISH SONG AS A LEARNING MEDIA OF LISTENING COMPREHENSION - Ester Sekeon; Paula Rombepajung; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
Song is one of the teaching tools that is utilized to aid in the development of the English language. The use of song in the classroom has numerous advantages for the learning process. Therefore, this study was conducted to see whether using songs in the classroom can provide benefits in the teaching and learning process. This research was conducted on 6th semester students majoring in English at UNIMA. In this study, the researcher used a survey method assisted by a questionnaire instrument which was distributed via google form as a platform for conducting interviews with objects. The subjects of this study were 18 students in 1 class. Based on what was found in the research, students agreed with the help provided by the song in the learning process. Students feel that their listening skill has improved because of listen to English song, because spending time with listen to English song make them more familiar with the English word, also make it easier to memorize a new vocabulary in the lyrics. They also feel enjoy in listen to English song because listen to a song make the atmosphere of learning become more relaxing. In general, the students responded positively to the assertions, with the majority agreed. The usage of English song can be useful in developing listening abilities, as evidenced by the preceding explanation.